Importance of posture in violin playing / Nur Hazwin Roslan - Roslan, Nur Hazwin (2013)
The study was carried out to determine the Importance of posture in violin playing in Faculty of Music, Universiti Teknologi Mara (UiTM) Shah Alam Selangor. Objective of this research is to describe the correct posture in violin playing, to investigate student's knowledge and understanding about the importance of posture in violin playing and to find out what are the effects of poor posture in violin playing and to find out what are the effects of poor posture in violin playing. The result shows that majority of the violinists in our faculty are not aware about the importance of posture due to lack of knowledge.